Muntz Rational Approximation for Special Function Classes in Orlicz Spaces (Analysis in Theory and Applications, 2017)
Using the method of construction, with the help of inequalities, we research the Muntz rational approximation of two kinds of special function classes, and give the corresponding estimates of approximation rates of these classes under wide conditions. Because the Orlicz Spaces is bigger than continuous function space and the Lp space, the results of this paper has a certain expansion significance.
Keywords: Muntz rational approximation; bounded variation function class; Sobolev function class; Orlicz space.